Knowledge and practice of galactogogues consumption among breastfeeding mothers in Kuantan, Pahang - Mahasan, Ainun Syuhada; Abdul Rahim, Norshuhaida; Tengku Azhar, Tengku Norbaya; Abdul Ghani, Radiah (Zes Rokman Resources, 2019)
It is well recognize that breast milk give many benefits to the infants. The best nutrition for early months of growth for normal infants is exclusive breastfeeding as suggested by World Health Organization (WHO). Almost all reasons that have been documented for discontinuance of breast milk are perception of insufficient production of milk. In order to increase the amount of milk, many breastfeeding mothers take an effort to take supplement, known as galactogogues which been claimed to increase quality and quantity of breast milk. However, the exact effect of galactogogues is still questionable. This study aims to determine the association between the effects of galactogogues on milk production and socio-demographic data, period of breastfeeding, practice of complementary breastfeeding or exclusive breastfeeding, problem during breastfeeding and frequency of consumption. This is a cross-sectional study and 120 respondents were selected by using purposive sampling. The result showed there was a significant association between effect of galactogogues consumption on milk production and period of breastfeed, inadequate breast milk supply and frequency of consumption (p<0.01). Food intake was the most significantly preferred as compared to herb and drug (p<0.01). There was a significant association between knowledge and practice of galactogogues consumption among breastfeeding mothers in Kuantan (p <0.05). In conclusion, knowledge of galactogogues consumption among breastfeeding mothers in Kuantan was good and the practice was prevalent among them.